Evaluating the defect targeting effects and osteogenesis promoting capacity of exosomes from 2D- and 3D-cultured human adipose-derived stem cells. (April 2023) - Chen, Ruijing; Feng, Taojin; Cheng, Shi; Chen, Ming; Li, Yi; Yu, Zihui; Xu, Ziying; Yin, Pengbin; Zhang, Licheng; Tang, Peifu
Abstract: Exosomes derived from stem cells show great therapeutic potential in bone defect repair. Systemic administration of exosomes represents as a minimally invasive delivery approach; however, evaluation for the lesion-targeting capacity and repair promotion efficacy lacks. In this study, exosomes produced by human adipose-derived stem cells (hADSCs) are intravenously injected to calvarial defect mice. It is found that exosomes preferentially accumulate at bone and especially at the calvarial defect site. In addition, exosomes treatment promotes osteogenesis as indicated by more newly formed bone at the lesion site. Furthermore, the impact of three-dimensional (3D) culture on hADSCs is evaluated by transcriptome sequencing and several pathways such as bone development, cartilage development are up-regulated in 3D-cultured hADSCs, suggesting an improved tissue repair capacity. Moreover, exosomes from 3D-cultured hADSCs show distinctly superior bone-targeting effects and bone repair capacity, as compared to those derived from 2D-cultured hADSCs. Collectively, this study highlights the bone-targeting and pro-osteogenic effects of hADSCs-derived exosomes, which could be further enhanced by 3D culture of the parental cells. Systemic injection of stem cell-derived exosomes could serve as a simple and minimally invasive approach to facilitate bone defect repair. Graphical Abstract: This study identifies a bone-targeting and pro-osteogenesis effect of exosomes produced by human adipose-derived stem cells (hADSCs) via intravenous injection to calvarial defect mice model. 3D hADSCs culture further promotes their exosomes' therapeutic efficacy in terms of lesion-targeting and bone defect repair. Systemic injection of exosome from 3D-cultured cells provides insights into the translation of exosome-based therapies with minimal suffering for patients in bone defect repair. The original elements used in the graphic abstract are from Servier Medical Art (http://smart.servier.com/). ga1 Highlights: Exosomes possess targeting effect towards bone and the defect site via intravenous injection. Systemic administration of exosomes could promote osteogenesis as indicated by more newly-formed bone at the lesion site. 3D culture of hADSCs could enhance the targeting and pro-osteogenesis effects of the derived exosomes. 3D culture of hADSCs could induce differential expression of exosome microRNAs associated with osteogenesis.